ŚLADY WIERZEŃ POGAŃSKICH NA PRZYKŁADZIE ZNALEZISK Z OSTROWA LEDNICKIEGO - BANASZAK, DANUTA; TABAKA, ARKADIUSZ (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2020)
The article presents an analysis of finds and information attributed to the pre-Christian religion in Ostrów Lednicki and the ancillary facilities. To this end, a number of finds from the first half of the 10th to the early 12th centuries were described and interpreted. They include a piece of a gold amulet locket, a utensil made of clay with the swastika and an encircled cross, a buried horse, wooden horse figures, an ornamental element of a knife sheath ferrule, a round rattle and a wooden structure with cornerstone offerings. By means of comparative studies and analyses of the archaeological excavations in Ostrów Lednicki and its vicinity (Dziekanowice, Moraczewo), the authors conclude that in this area, a pagan cult centre could have existed in the late 9th and the early 10th centuries at the latest, related most probably to Svarog /Svarozic, god of the Sun, the home, and a divine blacksmith.